Pengaruh E-Trust, Website Quality, E-Service Quality dan Keragaman Produk Terhadap Keputusan Pembelian - Cindy Kristianty Eka Wardhani; Edy Nursanta; Widiyarsih; Siti Masitoh (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
This study aims to analyze the influence of E-Trust, Website Quality, E-Service Quality, and Product Diversity on Purchase Decisions on Lazada.co.id in East Jakarta. The analytical method used in this study involves quantitative primary data, with the test phases including validity, reliability, normality, heteroscedasticity, multicollinearity, multiple linear regression, coefficient of determination, F-test, and t-test. The sample taken in this study consisted of 100 respondents, using purposive sampling as the sampling method. The results of the t-test showed that the calculated t-values were greater than the t-table values for the following variables: E-Trust (3.575 > 1.985), Website Quality (4.444 > 1.985), and E-Service Quality (2.418 > 1.985), indicating that these three variables partially influence Purchase Decisions on Lazada.co.id in East Jakarta. Meanwhile, Product Diversity had a calculated t-value smaller than the t-table value (0.378 < 1.985), meaning that the Product Diversity variable does not influence Purchase Decisions on Lazada.co.id in East Jakarta. The results of the F-test showed that E-Trust, Website Quality, E-Service Quality, and Product Diversity simultaneously influence Purchase Decisions on Lazada.co.id in East Jakarta, as indicated by the calculated F-value of 89.759 > 2.47.